MEASUREMENT OF THE AMPLITUDE OF PERIODIC SIGNALS USING THE FIBONACCI METHOD - V. S. Petrushak (Приборы и методы измерений)
Development of new methods and high-rate means for converting the amplitude of high-frequency periodic signals into a binary code with high speed for solving problems of industrial tomography, radar, radio navigation, during measurements of amplitude-frequency characteristics, measurement of the amplitude of signal generators is relevant in scientific terms and useful in practical applications. The aim of the study was to create a new amplitude meter for high-frequency periodic signals based on the Fibonacci method without converting the AC voltage into an equivalent parameter.Based on the developed algorithm and the equation for converting the amplitude of periodic signals into code using the Fibonacci method, a functional scheme of the amplitude converter has been developed. This made it possible to realize an 8-bit amplitude converter in code on the FPGA Cyclone V series of the Altera company. Amplitude converter of periodic signals into the code based on the Fibonacci method consists of: two comparators, a phase detector, a short pulse shaper, a digital-to-analog converter, a Fibonacci register, an extender, a clock counter, a decoder and an indicator. In the developed meters of the amplitude of the periodic signal, the process of forming the measuring periods and their calculation was applied, this made it possible to avoid the conversion of the alternating voltage into an equivalent parameter. The process of forming measurement periods and their calculation is realized on the basis of a comparator and a counter. The application of the Fibonacci register allowed setting the conversion time at the level of N/f (number of register bits / frequency of the incoming signal). Using the Fibonacci sequence of the pentanacci sequence in the basis of the work of the Fibonacci register allowed obtaining odd code values at its output.Based on the obtained research results, a high-resolution converter of the amplitude of high-frequency periodic signals can be developed into a binary code with high speed for tasks: industrial tomography, radar and radio navigation.